2019
DOI: 10.1080/13102818.2019.1606733
|View full text |Cite
|
Sign up to set email alerts
|

Types of microorganisms in proximal caries lesion and ozone treatment

Abstract: The purpose of this clinical study was to investigate the types of microorganisms in deep proximal caries lesions and the efficacy of elimination of microorganisms after a 24 s ozone application to proximal cavity lesions prepared for restoration. Sixteen caries-active volunteers (female: 8, male: 8; age range: 35-55), with proximally situated deep caries lesions on premolars or molars, were included in the study. Each patient underwent two microbiological investigations. First, the caries decay before treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…However, fewer studies investigated their cariogenic associations. Though S. salivarius and S. anginosus have been considered as oral commensal flora, some findings suggest that S. salivarius and S. anginosus isolated from deep proximal caries lesion could be considered as indices for caries activity [41,42]. Half a percent of sodium chloride and 2% of soy peptone were added into artificial saliva to simulate a real oral environment.…”
Section: Isolation and Identification Of Potentially Cariogenic Microorganismsmentioning
confidence: 99%
“…However, fewer studies investigated their cariogenic associations. Though S. salivarius and S. anginosus have been considered as oral commensal flora, some findings suggest that S. salivarius and S. anginosus isolated from deep proximal caries lesion could be considered as indices for caries activity [41,42]. Half a percent of sodium chloride and 2% of soy peptone were added into artificial saliva to simulate a real oral environment.…”
Section: Isolation and Identification Of Potentially Cariogenic Microorganismsmentioning
confidence: 99%
“…Gaseous ozone stimulates dentinogenesis [ 22 ]. Our studies have proven that 24 s of gaseous ozone application removes cariogenic microbes in the cavity after removing infected dentin; it has a disinfection effect [ 13 ]. Ozone administration has been shown to improve metabolism in inflamed tissues, enhance tissue oxygenation, and reduce inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Under anesthesia, pulp wound hemostasis and cavity disinfection with ozone gas was performed for 24 s using an ozone generator (Prozone, TIP TOP TIPS Sarl, Rolle, Switzerland) [ 13 ]. Venous blood (10 mL) was obtained from the patient by venipuncture and centrifuged at 1300 rpm for 14 min (Duo Centrifuge/Process for PRF, Nice, France).…”
Section: Methodsmentioning
confidence: 99%
“…Our study is based on the treatment of dentine wounds with ozone. Our previous studies found that gaseous ozone in 24 seconds destroys all microorganisms in the prepared cavity in deep approximal lesions [16,17]. Other authors found that remineralization improves the hardness of enamel and dentin after gaseous ozone application [18,19].…”
Section: Discussionmentioning
confidence: 99%